Hyposalinity affects diurnal photoacclimation patterns in the rhodophyte Palmaria palmata under mimicked Arctic summer conditions - Marambio Gallardo, Johanna Valeska; Rosenfeld, Sebastian; Bischof, Kai (My University, 2022)
Ocean temperatures have increased during 2011–2020, causing significant changes in the marine environment. One area that has been affected by the temperature increase is the Arctic, leading to a decrease in glacial mass and an increase in meltwater. Some organisms e.g., Fucus (brown seaweed) benefit from these environmental changes while others may be strongly affected. Palmaria palmata (Rhodophyta), an alga that inhabits the arctic, intertidal and upper subtidal zones, is directly influenced by variations in the daily cycles of irradiance and temperature and being affected by low salinities. Fronds of P. palmata were collected during the summer of 2019, in Kongsfjorden, Svalbard (78.9°N, 11.9°E). For 21 days at 0 °C, the material was subjected to variations in daily irradiance cycles reaching minimum values of 50 μmol photons m−2 s−1 and maximum values of 500 μmol photons m−2 s−1. These conditions were complemented with three different salinities SA 34 (control), 28, and 18. Subsequently, measurements of photosynthetic parameters such as Fv/Fm, NPQ, biochemical parameters such as pigment quantification (Chl a, Lut, Zeax, β-Car, PE, PC, APC), and antioxidant activity (DPPH) were carried out. In general, for P. palmata, salinity was the factor that negatively affected photosynthetic activity, with Fv/Fm showing a decrease in values towards the end of the experiment with SA 28 and 18. With SA 34, P. palmata can respond more effectively to variations in daily irradiance, whereas, as salinity decreases, its response capacity is diminished. These data are supported by variations in the daily pigment concentration of Chl a, β-Car, and Zeax, the latter occurring at low concentrations, showing variations in daily irradiance cycles at SA 28 and 18. Phycobilins, in general were found to be more sensitive to irradiance variations, while antioxidant activity - DPPH, was influenced by both daily irradiance cycles and low salinity. The physiological response of Palmaria palmata shows its tolerance to daily irradiance variation, which is restricted by decreasing salinity. This kind of acclimation to different factors may generate a high energy expenditure, which could be reflected in the growth rate of the species in the Arctic, leading to a decline of Arctic populations in the future.
Keywords: arctic; hyposalinity; irradiance; palmaria palmata; photosynthesis